Religion, the body, and sexuality - Hoel, Nina, author.
1 online resource.
Keywords: How does religion relate to bodies and sexualities? Many people would answer, simply, "through repression," but the relationship is much more complicated than that. While many religions draw boundaries between what they consider to be appropriate and inappropriate use of the human body, especially in the realm of sexuality, the same religions often celebrate human sexuality and even expect sexual partners to provide each other with sexual pleasure. Celibacy, too, is more than just repression, and sometimes it is even seen as providing the practitioner with great spiritual power; in other settings, the sex act itself is understood to provide this power. Religion, the Body, and Sexuality offers students and general readers a sophisticated and accessible exploration of the connections between religion, sexuality, and the body, through case studies and overviews in the following thematic chapters: Celibacy Regulation Controversy Violence Innovation Instrumentalization Ecstasy Each chapter includes suggestions for further reading, questions for further thought, and a list of relevant media resources. This engaging book is an excellent addition to introductory courses on religion or sexuality and is a much-needed new volume for advanced courses on the intersections of these areas of human experience.